Strengthening Impacts on the Auxiliary and Morphological Changes of TiO\(_2\) Degussa - Prasanna, D. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Titanium dioxide (TiO\(_2\)) is an uncommon class of metal oxides that are generally utilized in an assortment of photograph catalysis applications and items in the natural and vitality, including selfcleaning surfaces, hydrogen development and sun(solar energy) oriented vitality conversion. Herein, impact of strengthening treatment on the structure and morphology of TiO\(_2\) (P25) was evaluated. Powder X-ray diffraction, examining electron microscopy, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy investigation were led to assign the development and portrayal of the auxiliary, substance piece and morphology of TiO\(_2\). The strengthening temperature influences the crystalline measurements, structure and the morphology of the samples. Strengthening temperature of 500\(^°\)C is an ideal vale to keep up an exceptionally steady crystalline morphology and all around characterized particles of TiO\(_2\) (P25).